2007
DOI: 10.1002/jbm.a.31217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and microstructural properties of hybrid poly(ethylene glycol)–soy protein hydrogels for wound dressing applications

Abstract: Biomimetic hydrogel made of poly(ethylene glycol) and soy protein with a water content of 96% has been developed for moist wound dressing applications. In this study, such hybrid hydrogels were investigated by both tensile and unconfined compression measurements in order to understand the relationships between structural parameters of the network, its mechanical properties and protein absorption in vitro. Elastic moduli were found to vary from 1 to 17 kPa depending on the composition, while the Poisson's ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…The hydrolyzed soy protein was used because it was commonly blended with other polymers and macromolecules in electrospinning. 15 The mixture was heated at 90 C under stir for 1 h to obtain transparent soy protein solution. The solution was loaded into a syringe and electrospun under a voltage of 45 kV with a distance of 25 cm between the receptor and syringe needle.…”
Section: Electrospinning Of 3d Brous Soy Protein Scaffoldsmentioning
confidence: 99%
“…The hydrolyzed soy protein was used because it was commonly blended with other polymers and macromolecules in electrospinning. 15 The mixture was heated at 90 C under stir for 1 h to obtain transparent soy protein solution. The solution was loaded into a syringe and electrospun under a voltage of 45 kV with a distance of 25 cm between the receptor and syringe needle.…”
Section: Electrospinning Of 3d Brous Soy Protein Scaffoldsmentioning
confidence: 99%
“…This value is as high as those of previously reported natural polymer-based wound dressings. [32][33][34][35][36] The flexibility of sericin gel film in the wet state is a significant advantage in application of it as a wound dressing: the gel film can be easily handled by forceps or hands, cut into any shape using knives or scissors, and attached to curved surfaces. This property is explained by the existence of an elastic region in the stress-strain curve of the gel film (Fig.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…It is noteworthy that these properties of sericin gel film were achieved by physical intermolecular interactions among sericin molecules alone, whereas previously reported natural polymer-based materials generally employ chemical modifications, such as cross-linking or grafting. [32][33][34][35][36] This feature of sericin gel film has great significance in its application as a wound dressing because the toxicity problem caused by residual chemicals does not need to be considered. In fact, cell proliferation tests indicated that the sericin gel film showed no cytotoxicity.…”
Section: Cell Adhesion and Proliferationmentioning
confidence: 99%
“…Snyders et al [14] and Shingel et al [15] investigated hybrid hydrogels made of poly(ethylene glycol) and soy protein for moist wound-dressing applications and concluded that these hydrogels can be considered as a safe, biocompatible and inflammatory inert wound-dressing material. Santos et al [16] developed chitosan/soy (cht/soy)-based membranes as wound-dressing materials and showed that these new membranes possess the desired features for healing/repair stimulation, ease of handling, and final esthetic appearance, which are valuable properties for wound dressings.…”
Section: Soy Proteinmentioning
confidence: 98%